DISSEMINATION OF GENERAL BIOLOGY TEACHING MATERIALS IN THE COVID-19 PANDEMIC - Masdiana Sinambela; Mariaty Sipayung; Tonggo Sinaga (Jurnal Pelita Pendidikan, 2022)
General biology teaching materials are learning resources used by first batch students of all majors at the Faculty of Mathematics and Natural Sciences, Unimed. General Biology teaching materials based on current investigations, namely to respond to the industrial revolution 4.0 must be in accordance with the BSNP. This General Biology teaching material was validated by 2 lecturers who are in charge of the General Biology course. Dissemination to see the effectiveness of General Biology teaching materials through trials. The step was taken through a small group of 10 students who took the General Biology lecture, the result of which was to get an A grade of 80% and a B grade of 20%. The large group test of 43 biology students class of 2020 by giving a test, the results of which were 77% A, 21% B, and 2% C, means that the expected learning indicators have been achieved. General Biology teaching materials are distributed to General Biology lecturers. General Biology teaching materials are appropriate based on the National Education Standards Agency (BSNP).